Assessing Patients’ Perception on the Adoption of Electronic Health Record System in Public Hospitals In Ghana: A Case Study of Kwesimintsim Hospital - Georgina, katakity (University of Mines and Technology, Tarkwa. Ghana, 2024)
The integration of Electronic Health Record System (EHRS) System as substitutes for traditional record-keeping methods has attracted significant attention from both healthcare professionals and policymakers, due to their potential to improve the efficiency of the provision of health services. This study investigates patient perceptions regarding the adoption of Electronic Health Record System in the context of Ghana, drawing on survey data collected at Kwesimintsim Hospital and employing descriptive statistics for analysis. Specifically, the research examines the level of awareness as well as the perceived benefits and challenges associated with the adoption of Electronic Health Record System at Kwesimintsim Hospital. The findings identified benefits such as improved patient care, improved access to patient information, reduced waiting time, and an overall improvement in the quality of care provided. On the contrary, challenges identified include concerns related to data privacy, computer illiteracy, language barriers, compliance with security regulations, and general illiteracy. Patients’ lack of access to the system emerges as a major obstacle. Given these findings, the study recommends that, first, steps should be taken by health care professionals to instil confidence in patients regarding the protection of their data, thereby mitigating concerns around data security. Additionally, efforts should be directed toward educating patients about the functionality of the system, ensuring its ease of use and accessibility. These recommendations are expected to facilitate the adoption and effective utilization of Electronic Health Record System, thereby fostering advancements in healthcare delivery at Kwesimintsim Hospital and beyond.
Keywords: Electronic Health Record System; Healthcare; Health